Critical Pedagogy and the Ecuadorian Curriculum: A Systematic Review of the Implementation of Freirean Principles in Education - Remache Bunci, Manuel Gonzalo; Almeida-Pástor, Marcelo; Grijalva Rosero, Jeferson Marcelo; Guerra Gómez, Elvis Jair; Cerpa Flores, Jonathan Arturo (Revista Ecos de la Academia, 2024)
The study conducts a systematic review of the scientific literature relating Paulo Freire’s pedagogical approaches to the Ecuadorian curriculum. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology was used. Eight articles exploring the implementation of Freirean principles and their points of convergence with the educational system were selected and analyzed. The results reveal notable differences. Freire proposes a critical and liberating pedagogy that fosters critical consciousness, participation and transformation of power structures through dialogue and reflection. Although the curriculum guidelines include elements of social justice and cultural diversity, such as the recognition of indigenous and Afro-Ecuadorian narratives, classroom practice still focuses on traditional and reproductive approaches that prioritize memorized knowledge intermediation. Despite these differences, both approaches promote social justice and the formation of critical individuals. However, the curriculum faces structural and social obstacles that limit its ability to achieve the criticality advocated by Freire. The study suggests that the educational system could integrate more dynamic and participatory methods, aligned with Freire’s liberating pedagogy, to promote a transformative education that allows students to critically reflect and act in their social reality.